Eutectic Ionic Liquids for Lithium Batteries. (25th October 2017) - Huang, Qianwen; Gurkan, Burcu
Abstract : In this paper, we report the formation of a eutectic with binary ionic liquid (IL) mixture of 1-methl-1-propylpyrrolidinium bis(trifluoromethylsulfonyl)imide, [Pyr13][TFSI], and 1-ethyl-3-methylimidazolium dicyanamide, [emim][dca]. An increased conductivity of 24.51 mS·cm -1 and decreased viscosity of 16.12 cP at 25 °C are achieved with the eutectic mixture, in comparison to the commonly investigated [Pyr13][TFSI]. The conductivity decreases and the viscosity increases with the addition of bis(trifluoromethane)sulfonimide lithium salt (LiTFSI) at a concentration range of 0 – 1 M at 25 °C. A complex Li + solvation environment, preferring solvation mainly by [dca], was observed by Raman spectroscopy.